Object Oriented Analysis and Design Aplikasi Pasar Online: TONPASAR - Dimas Irmansyah; Aliya Zhafira Wastuyana; Elizabeth Alda Hermanto; Anindo Saka Fitri (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
As time goes by, traditional markets are starting to be abandoned by society because of the existence of modern markets, namely supermarkets, minimarkets and e-commerce. However, many goods can only be obtained in traditional markets and many of these goods are basic needs of society. Therefore, an application is needed that can facilitate traditional markets so that sellers and buyers are no longer abandoned, namely online market applications. The main aim of designing this application is to help traditional market sellers who were previously affected by a lack of buyers. Apart from that, this application can also benefit parties other than sellers, namely traditional market buyers who previously had problems accessing traditional markets or other obstacles. The design of this online market application uses the Object Oriented Analysis and Design (OOAD) method. By designing this application, it will really help traditional market sellers who were previously affected by a lack of buyers.